2002
DOI: 10.1128/aem.68.12.6283-6291.2002
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Streptococcus mutans Genes Are Involved in Biofilm Formation

Abstract: Streptococcus mutans has been strongly implicated as the principal etiological agent in dental caries. One of the important virulence properties of these organisms is their ability to form biofilms known as dental plaque on tooth surfaces. Since the roles of sucrose and glucosyltransferases in S. mutans biofilm formation have been well documented, we focused our attention on sucrose-independent factors. We have initially identified several mutants that appear to be defective in biofilm formation on abiotic sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
180
4
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(194 citation statements)
references
References 49 publications
5
180
4
3
Order By: Relevance
“…The order of adhesiveness of S. mutans to the different surfaces is polystyrene > HA > glass. This finding is also consistent with previous observations (Yoshida & Kuramitsu, 2002). COMSTAT analysis of S. mutans biofilm structures grown with indicated sucrose concentrations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The order of adhesiveness of S. mutans to the different surfaces is polystyrene > HA > glass. This finding is also consistent with previous observations (Yoshida & Kuramitsu, 2002). COMSTAT analysis of S. mutans biofilm structures grown with indicated sucrose concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…The most widely used is the microtiter plate assay for measuring the amount of biofilm formation (O'Toole & Kolter, 1998). Although not a means of direct measurement, this method has been used by a number of laboratories for screening mutants that affect biofilm formation (O'Toole & Kolter, 1998;Yoshida & Kuramitsu, 2002;Friedman & Kolter, 2004). Although semi-quantitative and easy to perform, the microtiter plate assay does not provide information on the kinetics of biofilm formation or the architecture of the biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the results of the animal experiment, that the dgk mutation did not effectively affect fissure caries formation, but drastically reduced smooth-surface caries formation, decreased sucrosedependent colonization of the dgk mutant may contribute to a decrease in S. mutans infection levels. However, in vitro experiments revealed that the dgk mutation did not affect sucrose-dependent biofilm formation at all, while a slight effect on glucose-dependent (without sucrose) biofilm formation was observed (data not shown), consistent with the result of the previous study (Yoshida & Kuramitsu, 2002). These results suggest that the Dgk may be not involved in sucrose-dependent colonization of S. mutans in vitro.…”
Section: Discussionsupporting
confidence: 82%
“…Streptococci are also known to aggregate to form oral biofilms; for instance, S. mutans rapidly increases biofilm thickness by producing surface-associated and biofilm regulatory proteins [7,9,10]. As such, reducing the size of cariogenic bacterial populations and suppressing biofilm formation are essential strategies for the prevention of oral diseases [11].…”
Section: Introductionmentioning
confidence: 99%